2017
DOI: 10.1111/1471-0528.14560
|View full text |Cite
|
Sign up to set email alerts
|

Current insights into the aetiology, pathobiology, and management of local disease recurrence in squamous cell carcinoma of the vulva

Abstract: A review that discusses the key prognostic factors that influence local recurrence in vulval cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…Consistent with these findings, a study of 405 New Zealand women with vulvar HSIL showed a risk of progression to malignancy of 5% of patients who received treatment versus 15% for those patients who were managed expectantly 26. dVIN accounts for a minority of the total number of VIN cases but is present adjacent to the invasive component in >40% of vulvar squamous cell carcinomas 27. This suggests that dVIN is associated with more rapid progression to invasive disease and/or the diagnosis is missed because of its subtle histopathological features.…”
Section: Methodsmentioning
confidence: 75%
“…Consistent with these findings, a study of 405 New Zealand women with vulvar HSIL showed a risk of progression to malignancy of 5% of patients who received treatment versus 15% for those patients who were managed expectantly 26. dVIN accounts for a minority of the total number of VIN cases but is present adjacent to the invasive component in >40% of vulvar squamous cell carcinomas 27. This suggests that dVIN is associated with more rapid progression to invasive disease and/or the diagnosis is missed because of its subtle histopathological features.…”
Section: Methodsmentioning
confidence: 75%
“…The higher incidence of vulvar SCC among patients with LS has been suggested to relate to the molecularly altered epithelium generated as a result of chronic inflammation with abnormal cytokine and growth-factor production (7). It has been shown that melanocytic naevi on LS lesions differ from ordinary naevi: they contain abundant melanin, diffusely express HMB-45, and have a higher Ki-67 labelling index (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that surgeons should aim for tumor‐free pathological margins of 8 mm or more to minimize local disease recurrence. Multiple retrospective studies have tried to assess the factors that may determine vulvar recurrence, and other clinical determinants besides inadequate excision margins have been suggested, although it is unclear which combination of factors is most significant …”
Section: Surgical Management Of Vulvar Squamous Cell Carcimomamentioning
confidence: 99%
“…As most vulvar squamous carcinomas arise in a background of atypical skin such as HSIL, lichen sclerosus, and dVIN, and as they characteristically recur locally but often at sites remote from the original tumor, it is suggested that many “recurrences” may actually be second primary tumors, which arise in a “field of cancerization”—an area of genetically‐altered preneoplastic epithelium that has the predisposition to undergo malignant transformation …”
Section: Surgical Management Of Vulvar Squamous Cell Carcimomamentioning
confidence: 99%